Innovation of Local Government in Creating Conducive Investment Climate (Study in Lamongan Regency) - Khoiri, A. Miftakhul (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
Local government needs innovation to solve public problems, one of them is investment climate. The problems related to investment climate include no security and weak rule of law, lack of infrastructure, las well as ong and complicated bureaucracy. Lamongan Regency is trying to create innovative programs to solve investment problems. Those innovations include Regional Regulation No. 2 of 2015 and Regent Decree number 23 of 2015, proactive service, fast service package, SMS Gateway, facilitation of land acquisition and gathering with investors. Through these various innovations, Lamongan government was awarded as East Java Investment Award 2015 from the Governor of East Java, with first honors for the category of investment performance.